2012
DOI: 10.1016/j.lwt.2011.10.024
|View full text |Cite
|
Sign up to set email alerts
|

UV-C treatment of soymilk in coiled tube UV reactors for inactivation of Escherichia coli W1485 and Bacillus cereus endospores

Abstract: Coiled tube UV reactors were used to investigate the influence of tube diameter (1.6 mm ID, and 3.2 mm ID) and Reynolds number (Re) to inactivate Escherichia coli W1485 and Bacillus cereus spores in raw soymilk (RSM). Four levels of Re (343, 686, 1029 and 1372) were tested in RSM inoculated separately with each bacterium and treated in the UV reactors at a constant residence time of 11.3 s with UV-C dose of 11.187 mJ/cm 2 at 253.7 nm. Inactivation efficiency of both microorganisms increased with Re. Maximum r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 32 publications
1
48
0
2
Order By: Relevance
“…Entre los métodos físicos utilizados para la inactivación de esporas de B. cereus, se ha reportado el tratamiento de leche de soya con radiación UV-C [90]. Además, se comparó el tratamiento térmico con la radiación con un haz de electrones, observándose que este último fue más efectivo para inactivar células vegetativas y esporas de B. cereus [91].…”
Section: Prevención Y Controlunclassified
“…Entre los métodos físicos utilizados para la inactivación de esporas de B. cereus, se ha reportado el tratamiento de leche de soya con radiación UV-C [90]. Además, se comparó el tratamiento térmico con la radiación con un haz de electrones, observándose que este último fue más efectivo para inactivar células vegetativas y esporas de B. cereus [91].…”
Section: Prevención Y Controlunclassified
“…This process would create the mixing effect and extra resident time in order for the pineapple juice to pasteurize (Muller, et al, 2011). The UV reactor was wrapped with aluminum foil for safety measured (Bandla et al, 2012). The frequency of the pump was set to 30, 35 and 40 Hz to adjust the flow rate of the juice.…”
Section: Ultraviolet Treatmentmentioning
confidence: 99%
“…The UV-C dose was calculated using Eq. (3) (Chia et al, 2012;Bandla et al, 2012) by multiplying the residence time with the irradiance intensity at pineapple juice surface, that was measured using UV radiometer (UVX Radiometer, UVP Company, US).…”
Section: Ultraviolet Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several literatures have been published on Dean flow UV reactor (Feng et al, 2013;Bandla et al, 2012;Choudhary et al, 2011;Muller et al, 2011;Franz et al, 2009;Ghaly and Singh, 2007) with various configurations and samples. However, only Muller et al (2011) reported the effect of absorptive and physicochemical properties of naturally cloudy apple juice, blood orange juice and elderberry nectar on the inactivation of pertinent microorganisms utilizing a UVivatec Lab System (Bayer Technology Services GmbH, Germany).…”
Section: Introductionmentioning
confidence: 99%